Synthesis of Anhydrous Dicalcium Phosphate for Precursor of Natural Ceramic Apatite Material - Muhammad Syaifun Nizar; Rizky Berliana Wijayanti; Kristanto Wahyudi (Jurnal Keramik dan Gelas Indonesia, 2020)
Dicalcium phosphate is one of the apatite materials used for precursors to synthesize other apatite materials such as tricalcium phosphate, tetracalcium phosphate, and hydroxyapatite. Apatite materials are widely used in the medical field and pharmaceutical industry. This study aims to prepare dicalcium phosphate from natural limestone as a precursor for apatite with an easy-to-apply method for industrial scale. Wet precipitation process was performed to prepare dicalcium phosphate from phosphoric acid and slaked lime or calcium hydroxide with reaction temperature control at around 60⁰C and at pH of 3-4, then drying is carried out at about 180⁰C. The product is characterized for its mineral content by XRD and EDX. Semi-quantitative calculation of the synthesized material contains more than 90% dicalcium phosphate andhydrous, the rest is other apatite minerals. It can be used as a precursor for apatite production.